Soccer fundamentals for players and coaches - Coerver, Wiel. Dec 3, 1924 - Apr 22, 2011; Coerver, Wiel. (Englewood Cliffs, N.J. : Prentice-Hall, 1986)
Wiel Coerver, one of the most effective soccer instructors of all time, has captured all the winning techniques and training methods he has developed over his many years of experience. You get everything you need to master the fundamentals, develop flexibility and agility and gain the tactical skills used by the world's top players.
Translation of: Leerplan voor de ideale voetballer
Keywords: Soccer; Soccer -- Coaching